BERBAGAI PILIHAN NILAI MORAL DALAM CERITA WAYANG - Ibnu Rochim, Achluddin; Jupriono, D. (COMMUNITY OF RESEARCH LABORATORY SURABAYA, 2022)
The immortality and greatness of puppet stories make many people to take them as the vital source in searching values for ethic and character education. Through this study, it will show that gods and punakawan stories, as well as both Ramayana and Mahabharata epics, do not only just provide story particles which contain constructive values (to develop character), but also destructive (to destroy character) and dillematic-existential (difficult to decide value preference). The varied values contained there, cause children to be confused in choosing and searching model. Therefore it needs selection, modification, and adaptation which are proportional-contextual in presenting gods and punakawan stories, as well as Ramayana and Mahabarata epics, for education of moral and character values toward Indonesian children.